#TITLE_ALTERNATIVE# - Arsil (NIM.253 97 034), Poppy
Abstract: Bilih is known as the origin species in Singkarak Lake. It must be protected because of its rare. The are two important things can disturb the sustainable of Bilih. First, Bilih exploitation by the fishermen and the other thing is natural disaster that we call Bangai. The Bangai occurs one time in 2 years. Because of these, there are 3 purposes to reach through this research. First, to know the significant water quality parameter in Bangai condition and normal condition. Measurement of water quality was done at Health Laboratories, Gunung Pangilun Padang. Second, to know the maximum sustainable level, optimal level and bionomic level. The control parameter of these are reserve of source, capture level and capture effort level. Third, to know the total economic value of Bilih as the social cost to support cost benefit analysis. We can use all of this as the management tool to decide the best alternative to manage the source of the fish. The result of the water quality measurement shows us there are four parameters offer water quality standard for fisheries and poultry. They are Free ammonia, phenol, Pb and Zn.The research has done in three sampling point, middle of the lake -300 meters from Pasir Singkarak village- in 11 meters depth (Code I), border of Pasir Singkarak village (Code II) and border of Ombilin village (Code III). Over fishing analysis used dynamic liner bio economic equation with time series data between 1988- 1998. The results of the equation are MSY level, optimal level and bionomic level. Reserve of Bilih in MSY balance (X MSY) 673.4726475 ton, capture MSY (Y MSY) 778.31 ton, capture effort MSY (E MSY) 5264 unit. In bionomic balance produced reserve bionomic (X ) 860.475, capture bionomic (Y ) 718.37 ton and capture effort (E MSY) 3803 units. The optimal balance at 25 % interest result reserves optimal (X ) 1088.52 ton, capture optimal (Y ) 482.88 ton and capture effort (E ) 2021 units. In 1998, Capture level has exceed capture bionomic and optical but not capture MSY. Its cause economical over fishing but not biological over fishing. Total economic value of the Bilih is Rp 19.857.440.990 with total use value is 11.624.055.090 and total non-use value 8.233.385.901